The use of fibrin and poly(lactic-co-glycolic acid) hybrid scaffold for articular cartilage tissue engineering: an in vivo analysis - Sha'ban, Munirah; Kim, Soon Hee; Idrus, Ruszymah; Khang, Gilson (AO Research Institute Davos, 2008)
Our preliminary results indicated that fibrin and poly(lactic co-glycolic acid) (PLGA) hybrid scaffold promoted early chondrogenesis of articular cartilage constructs in vitro. The aim of this study was to evaluate in vivo cartilaginous tissue formation by chondrocyte-seeded fibrin/PLGA hybrid scaffolds. PLGA scaffolds were soaked carefully, in chondrocyte-fibrin suspension, and polymerized by dropping thrombin-calcium chloride (CaCl2) solution.PLGA-seeded chondrocytes were used as a control. Resulting constructs were implanted subcutaneously, at the dorsum of nude mice, for 4 weeks. Macroscopic observation, histological evaluation, gene expression and sulphated-glycosaminoglycan (sGAG) analyses were performed at each time point of 1, 2 and 4 weeks postimplantation.Cartilaginous tissue formation in fibrin/PLGA hybrid construct was confirmed by the presence of lacunae and cartilage-isolated cells embedded within basophilic ground substance. Presence of proteoglycan and glycosaminoglycan (GAG) in fibrin/PLGA hybrid constructs was confirmed by positive Safranin O and Alcian Blue staining. Collagen type II exhibited intense immunopositivity at the pericellular matrices. Chondrogenic properties were further demonstrated by the expression of gene encoded cartilage-specific markers, collagen type II and aggrecan core protein. The sGAG production in fibrin/PLGA hybrid constructs was higher than in the PLGA group. In conclusion, fibrin/PLGA hybrid scaffold promotes cartilaginous tissue formation in vivo and may serve as a potential cell delivery vehicle and a structural basis for articular cartilage tissue-engineering.